Impact of Tigris River Pollution on the Performance of Water Treatment Plants Efficiencies in Baghdad City - N. Hamza, Janan (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The determination of river pollution impact on the performance of water treatment plants is achieved by two main objectives. The first is to study raw and treated water qualities and comparing them with standards and the second is to evaluate the treatment plants efficiency. The analyzed data were those water quality parameters in relation to physical, chemical and bacteriological characteristics for river water and produced water by seven water treatment plants located on Tigris River passing through Baghdad City.The results of this study indicated that all raw water characteristic are within the surface water standards established by Iraqi and USA criteria except Bacterial Counts.Tigris River water is of good quality to be treated at the intake of KWTP and tends to be of less quality as it flows to south of city, where it is highly polluted at intake of RWTP.The analysis of treated water quality parameters supplied by all water treatment plants indicated that most of these characteristics are within the Iraqi criteria and WHO guide lines except for the produced in RWTP.RWTP exceeded the water quality standards which recommended by WHO particularly Bacterial Counts and Turbidity.The analysis showed that all water treatment plants have little effect on the in removal of the most of inorganic chemicals pollutants, the increasing Level of Sulfate, Hardness, and Total Dissolved Solid in treated water could be related to the absence of any chemical treatment units in the conventional Baghdad water treatment works, and to the increasing of the concentration of these variables in river water.The statistical analysis had indicated that the correlation coefficient between Turbidity and Total Coliform Bacteria in river water for KWTP, EWTP and KRWTP were good, and begin to increase at other water treatment plants reaching RWTP because the water quality of the river is deteriorated as the river flow downstream in Baghdad city.